Intravenous Administration of Cisplatin with Magnesium Sulfate Supplement May Prevent Kidney Toxicity in Rats: The Role of Gender and Magnesium Sulfate Dose. (16th February 2022) - Pournaderi, Parisa; Pourvali, Behnaz; Ashrafi, Farzaneh; Talebi, Ardeshir; Pezeshki, Zahra; Nematbakhsh, Mehdi
Abstract : Background . Cisplatin (CP) is widely used to treat various kinds of malignancies, but to avoid its side effects of nephrotoxicity and hypomagnesemia, magnesium supplementation is a subject of debate . The current study was designed to determine the protective role of intravenous magnesium sulfate (MgSO4 ) against intravenous administration of CP in male and female rats. Method . In this case-control experimental study, 80 Wistar male and female rats in 12 groups of experiments were subjected to receive intravenous administration of CP accompanied with intravenous infusion of different doses (1, 3, and 10 mg/ml solution) of MgSO4 and were compared with the control groups. Results . CP administration increased blood urea nitrogen (BUN), creatinine (Cr), kidney tissue damage score (KTDS), and kidney weight (KW), and they were attenuated by the mid-dose of MgSO4 supplementation in female rats. However, in male rats, the increase of Cr, BUN, KTDS, and KW induced by CP was ameliorated by low, mid-, and high doses of MgSO4 supplements. The levels of these markers were significantly different between male and female rats in the mid-dose of MgSO4 -treated group (BUN: P = 0.002, Cr: P = 0.005, KTDS: P = 0.002, and KW: P = 0.031 ). CP reduced clearance of Cr (ClCr) in both male and female rats significantly compared to the control group of saline alone ( P male  = 0.002 and P female  = 0.001), and the mid- and high doses of MgSO4 supplements improved ClCr in female rats. There were also sex differences in ClCr in mid- (P = 0.05 ) and high (P = 0.032 ) doses of MgSO4 -treated groups. CP accompanied with the mid-dose of MgSO4 supplement reduced the KTDS ( P male  = 0.04 and P female  = 0.004) and KW ( P male  = 0.002 and P female  = 0.042) in both male and female rats significantly when compared with the CP-alone-treated group, while there were also significant differences between the sexes (KTDS: P = 0.002 and KW: P = 0.031 ). CP accompanied with three different doses of MgSO4 supplements did not improve the serum levels of lactate dehydrogenase, urine level of sodium, malondialdehyde, urine flow, and nitrite statistically when compared with the CP-alone-treated group. Conclusion . The renal protective effect of MgSO4 could be dose and gender related.